Challenges and Issues of Anti-SARS-CoV-2 Vaccines - Blumental, Sophie; Debré, Patrice (Frontiers in Medicine, 2021)
At the beginning of 2021, anti-SARS-CoV-2 vaccination campaigns have been launched in almost 60 countries with more than 100 billion of doses distributed. In addition to the few vaccines already administered, many other candidates are in preclinical phases or experimental stages in humans. Despite availability of anti-SARS-CoV-2 vaccine constitutes a major advance and appear the only way to control the pandemic, some interrogation remains notably about the impact on transmissibility, the duration of the conferred protection in mid- and long- term, the effectiveness against present and future viral mutants or the ideal schedule to apply. In this paper, we review the circumstances that facilitated such a fast development of anti-SARS-CoV-2 vaccines and summarize the different vaccine platforms under investigation as well as their present results and perspectives in different settings. We also discuss the indications of vaccination in special conditions like history of previous COVID-19 infection or belonging to extreme age categories like children and elderly. Overall, this review highlights the multiple challenges to face if aiming to find a global solution to the pandemic thanks to high vaccine coverage all over the world.